GLYCEMIC CONTROL OF TYPE 2 DIABETIC PATIENTS DURING RAMAZAN FASTING - Malik, Uzma; Mahmood, Nasir; Khan, Khurshid Ahmed; Hameed, Maliha; Randhawa, Fawad Ahmed; Salman, Sadia; Riaz, Amna; Waheed, Khadija; Rasheed, Aqeela (Journal of Ayub Medical College Abbottabad, 2017)
Background: Among five main pillars of Islam Fasting is one of the key elements, all healthy adult Muslims have to observe fast from dawn till dusk during the holy month of Ramadan. According to a 2009 demographic study, Islam has 1.57 billion believers, making up 23% of the world population of 6.8 billion, and is growing by 3% per year. EPIDIAR (epidemiology of diabetes and Ramadan) study showed that 43% patients with type 1 and 79% patients with type2 diabetes observe fast during the month of Ramadan. Whereas those people who are suffering from diabetes and are fasting may be at risk of adverse outcomes and the risks may rise with longer fasting periods. Ideal management of diabetic patients who wish to fast during Ramadan needs to be done to avoid the complications. The purpose of this study was to observe the effect of fasting on glycaemic control in type 2 diabetic patients during the month of Ramadan. Methods: This was an observational cross sectional study; it was conducted at outpatient department Jinnah institute of diabetes and endocrinology Jinnah hospital Lahore during the month of Ramadan. Patients were advised to monitor blood sugar levels for two days before and after three meals (lunch, breakfast and dinner) before Ramadan and then during Ramadan blood sugar levels were monitored for four days in first Ashra before and two hours after Sehari, for four days at noon during second Ashra and then for four days pre and two hours after Iftar in last Ashra of Ramadan. Patients were educated Pre-Ramadan about glucose monitoring and drug dosage adjustments were done along with dietary counselling. Results: Blood glucose levels two days before and during Ramadan fell within range of mean glucose level of 150-187 mg/dl showing no extreme fluctuations in blood glucose levels only one patient reported symptomatic and biochemical hypoglycaemia severe enough to break the fast at noon. Conclusion: We concluded that in Ramadan fasting, type 2 diabetic patients with proper education, dietary counselling and drug dosage adjustments glycaemic control can remain in safe acceptable range preventing any life-threatening complication. Keywords: Type 2 Diabetes; Fasting; Ramadan; Glycaemic control